(untitled) (Recoletos Multidisciplinary Research Journal, 2025)
Background: Body Dysmorphic Disorder Risk (BDDR) may incite Body Dysmorphic Disorder (BDD) following bodily imperfection fixations, potentially fuelling Exercise Addiction (EA) ? excessive exercising causing musculoskeletal disorders. This study examined the correlation between BDDR and EA, their prevalence among Regular Exercisers (REs), and BDDR’s significant association with age, sex, and exercise dynamics. Methods: A descriptive-correlational design was employed. BDDR was assessed using a BDD questionnaire, and EA was measured with the Exercise Addiction Inventory. Pearson’s correlation determined the relationship between BDDR and EA, while prevalence was calculated using frequencies and percentages. Chi-square tests assessed associations between BDDR and demographic or exercise-related variables. Results: Among the 179 respondents, REs showed a low prevalence of BDDR and a moderate prevalence of EA. BDDR was significantly associated with age, exercise frequency, and duration (p < 0.05). Respondents with BDDR reported concerns with body build, shape, and weight. Age emerged as a predictor of BDDR, and adjusting exercise frequency and duration appeared to reduce BDDR risk. While EA and BDDR can co-occur, they are not mutually predictive. Conclusion: The findings highlight the importance of balanced exercise practices that promote physical and psychological well-being while guiding future research toward exploring additional physiological and psychological contributing factors to BDDR.